'Smart food city': Conceptual relations between smart city planning, urban food systems and innovation theory. (March 2019) - Maye, Damian
Abstract: This paper develops a conceptual link between smart city planning and urban food systems research in terms of governance and innovation. The 'smart city' concept is linked to an urban research agenda which seeks to embed advances in technology and data collection into the infrastructures of urban environments. Through this neoliberal framework, market-led and technological solutions to city governance and development are prioritised. The urban food movement has a different trajectory compared to the smart city agenda, comprising a diverse mix of urban food production practices, including community and grassroots-based social innovations, and associated more recently with food security discourses. Recognising these ideological and epistemological differences (between the smart city and the urban food movement) is important for conceptualisations of 'smart food city' governance. Based on theoretical reflections, review material and findings from a European project on city-region food systems, the paper argues that smart technology can be an important part of the solution to city food challenges but in combination with social innovations to enable flexible modes of governance that are inclusive, technologically and socially-orientated and linked to specific city-region contexts. Key elements include city regionalism, new organisational structures and connectivities, a circular model of metabolism and social practices. Highlights: Develops a conceptual link between smart city planning and urban food systems in terms of governance and innovation. There are ideological and epistemological differences between the smart city and urban food systems research. The 'smart city' concept embeds advances in technology and data collection into the infrastructures of urban environments. Urban food comprises diverse food production practices and is increasingly framed by food security discourses. Smart technology is an important part of the solution to city food challenges but in combination with social innovations.